Influence of meteorological conditions in autumn/winter 2021–2022 on the development of storm surges and the dune erosion on the Polish Baltic coast as a result of climate . . . . 93 - Łabuz, Tomasz Arkadiusz (Studia Quaternaria, 2023)
This paper presents details of 37 storm surges that occurred on the Polish southern Baltic Sea coast in the autumn/winter 2021–2022 season. They emerged during the passage of a larger number of low-pressure systems than usual from the SW-W direction over the Baltic Sea. Based on an assessment of meteorological and hydrological conditions during the storms, the relationship between the wind parameters, the sea level increase, and its maximum elevation was ascertained. The relationship between the sea level and the run-up elevation was ascertained. The elevation of the sea level and run-up on the onshore were compared with the beach height. Sections with a lower beach were affected by dune erosion already at a lower sea level. The dependence of dune erosion on the sea level elevation was presented. The value of the dune base retreat depended on the beach elevation and the sea level expressed by the onshore flow called run-up. The most significant erosion occurred during the storm Nadine with a sea level of 1.0–1.28 m AMSL. The average erosion varied between 1.0 and 4.5 m. The maximum erosion values reached 8–13 m.
Keywords: storm surges; run-up; wind force; low-pressure systems; dune retreat